Critical Discussion of Exclusion and Inclusion in CNN Indonesia Online News: Theo Van Leeuwen's View - Ita Putriani; Novia Juita (Pusat Kajian Humaniora FBS Universitas Negeri Padang, 2021)
Critical theory is used as a tool to study the problem of clashes between Asmat residents and Fayit Koramil members. Basically, this research emphasizes more attention on Asmat residents who experience marginalization in social life. The purpose of this study was to analyze criminal news under the title